Educative Game Tools Based On Environmental Materials In Over-coming Learning Problems Early Childhood Education Programs - Mamah Rahmah Dewi (Eduvest - Journal of Universal Studies, 2023)
The implementation of Early Childhood Education needs serious attention because many early childhood education organizations still do not meet quality standards, the reason is that there are still limited Educational Game Tools used by education in the implementation of learning. So this study aims to find out the Environmental Material-Based Educational Game Tool in overcoming the learning problems of early childhood education. This study uses a type of qualitative research with a documentation method. The data analysis technique used in this study is Miles and with four stages, namely 1) data collection, 2) data reduction, 3) data presentation, and 4) verification or conclusion. The results of the study show that educational game tools based on environmental materials are easy to obtain, so they can overcome the problems of early childhood learning. One example of an Educational Game Tool is Mekuo-kuo or commonly called congklak.